(3cJGH GdbeQs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI (B: (3agPG gh GdcJGH dGSGHY ef cJHfG GdSHYI GdeSei HcJGH GdbeQ s
(3BNQgG (B:s
(3hbGd ai cJGH GdCUdGM ai JOHjQ GdedM ef GdJbWjQ hGdJQUjU hGdJQcjH ecJhH ai QSGdI CNQi adjQLY EdjgG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B233 - (3U(B234s
(3GdfSNI HgG MhGTs
(3hgh GdcJGH GdSGHY ef cJGH GdHQgGf ai CSQGQ Yde GdejRGfs
(3jHOh Cf eG ChQOg GdfGSN ef cJGH GdbeQ YHGQI Yf JdNjUGJ eJaQbI NJegG HgPg GdYHGQI hHeG PcQfGg CcJH cJGH GdaVI hGdSdGes
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs